2019
DOI: 10.1089/neu.2017.5449
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Multivariate Proteomic Panel for Traumatic Brain Injury Biomarker Discovery: A TRACK-TBI Pilot Study

Abstract: The complex and heterogeneous nature of traumatic brain injury (TBI) has rendered the identification of diagnostic and prognostic biomarkers elusive. A single acute biomarker may not be sufficient to categorize injury severity and/or predict outcome. Using multivariate dimension reduction analyses, we tested the sensitivity and specificity of a multi-analyte panel of proteins as an ensemble biomarker for TBI. Serum was collected within 24 h of injury in a cohort of 130 patients enrolled in the multi-center pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…ED admission levels of CRP predicted the presence of postconcussion symptoms at 3 months postinjury in a cohort of adult patients with mTBI . Inflammatory markers contributed to a multivariate predictor model for recovery at 3 and 6 months postinjury in an ED sample of mostly mTBI patients . Tumor necrosis factor levels at 1 to 4 days postconcussion were elevated in pediatric mTBI patients that developed persistent symptoms at 1 month postinjury .…”
Section: Discussionmentioning
confidence: 91%
“…ED admission levels of CRP predicted the presence of postconcussion symptoms at 3 months postinjury in a cohort of adult patients with mTBI . Inflammatory markers contributed to a multivariate predictor model for recovery at 3 and 6 months postinjury in an ED sample of mostly mTBI patients . Tumor necrosis factor levels at 1 to 4 days postconcussion were elevated in pediatric mTBI patients that developed persistent symptoms at 1 month postinjury .…”
Section: Discussionmentioning
confidence: 91%
“…For example, similarities exist between post-traumatic symptomatology and cognitive or behavioral changes that arise from other inflammatory conditions, such as sepsis [40]. Interestingly, a recent study has shown that using an unsupervised multivariate approach applied to a multi-analyte proteomic panel, including several inflammatory markers, it was possible to fairly accurately predict positive CT-findings and outcome in a study sample that consisted predominantly of mild TBI patients, although 42% of these patients had lesions on CT [42].…”
Section: Inflammationmentioning
confidence: 99%
“…Proteomic research on neural diseases has mainly focused on neurodegenerative diseases, such as Alzheimer’s disease and Huntington’s disease [ 34 36 ], epilepsy [ 37 ], narcolepsy [ 38 ], and ischemic cerebral disease [ 39 , 40 ]. As for TBI, proteomics has been primarily applied to discover new biomarkers [ 41 , 42 ]. In particular, Cheng et al found that targeted temperature management (TTM) prevented TBI-induced neuronal necrosis, neuronal death, and brain edema, and some altered proteins (i.e., plasminogen, antithrombin III, and transthyretin) were identified [ 43 ].…”
Section: Introductionmentioning
confidence: 99%